2006
DOI: 10.3892/or.16.4.845
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs 143 and 145 are possible common onco-microRNAs in human cancers

Abstract: Abstract. MicroRNAs (miRNAs) are endogenously expressed RNAs 18-24 nucleotides in length that regulate gene expression through translational repression by binding to a target mRNA. It is thought that the expression level of miRNAs, which act like antioncogenes, is frequently reduced in cancers because of chromosome deletion and epigenetic changes. Since the processing of miRNAs has been characterized to be enzymatic in nature, the expression levels of miRNAs are closely associated with the activity and levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
214
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(241 citation statements)
references
References 14 publications
22
214
1
4
Order By: Relevance
“…Previously, we reported that miR-143 and -145, which are localized at 5q32 and possibly transcribed as the same primary miRNA, 9 were downregulated in six patients MicroRNA-143 and -145 in human colorectal tumors Y Akao et al with colon cancers; 7 and we found that they function as anti-proliferative miRNAs based on the results of experiments using human colon cancer DLD-1 cells transfected with either miRNA. In this study, the expression levels of miR-143 and -145 in 128 clinical samples of cancers and adenomas were examined by performing TaqMan miRNA assays using real-time PCR.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Previously, we reported that miR-143 and -145, which are localized at 5q32 and possibly transcribed as the same primary miRNA, 9 were downregulated in six patients MicroRNA-143 and -145 in human colorectal tumors Y Akao et al with colon cancers; 7 and we found that they function as anti-proliferative miRNAs based on the results of experiments using human colon cancer DLD-1 cells transfected with either miRNA. In this study, the expression levels of miR-143 and -145 in 128 clinical samples of cancers and adenomas were examined by performing TaqMan miRNA assays using real-time PCR.…”
Section: Discussionmentioning
confidence: 74%
“…We further confirmed that among the various synthetic miR-143BPs the miR-143BP/ 3 0 -2 M was the most potent for the suppression of the protein expression of ERK5, which was previously determined to be one of the major target genes of miR-143 (Figure 2c). [7][8][9][10][11] In contrast, the level of ERK5 mRNA was almost unchanged with all the synthesized miR-143s tested by semi-quantitative reverse transcription PCR (data not shown). Thus, such a modification and change in the duplex structure in miR-143 was closely associated with the potency of its growth-suppressive effect on DLD-1 cells.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations